Training On Coffee Processing And Packaging In Improving The Competitiveness Of Local Products In Bukit Tinggi Tourist Village - Hariani, Yuni Sulpia; Fauzi, Agus Khazin; Budiman, Budiman; Anwariyah, Komariyuli; Farha, Farha (UNIVERSITAS MUHAMMADIYAH MATARAM, 2025)
Bukit Tinggi Village is one of the Tourism Villages in Gunung Sari District, West Lombok Regency. As one of the tourist villages that has natural and artificial attractions, it is important for the village to continue to develop a green and sustainable quality tourist village to realize the prosperity of the village. To support this, superior products owned by Bukit Tinggi Village need to be echoed so that they are recognized by the wider community, one of which is coffee products. Many people have so far only processed coffee for personal or family consumption, even though the coffee land and coffee flavor of Bukit Tinggi Village are not inferior to other areas. To support coffee processing, which is still traditionally processed, the Community Service Team from Politeknik Negeri Bali PSDKU West Lombok in collaboration with the West Lombok Tourism Office conducted training and coffee packaging to increase the competitiveness of local products. The purpose of this community service activity is to assist the community in developing coffee processing and packaging so that it has a high selling value. In addition to assisting in the development of coffee processing, the Community Service Team also helps in terms of education on the use of brands/labels, packaging, marketing and determining a fair market price. This is because so far most of the people of the coffee products produced in relation to brand/label, packaging, marketing, and determining a fair market price. The method used in this community service activity is training or direct demonstration with service participants.The results of this community service that have been carried out are the insights and knowledge of the community regarding coffee processing in a modern way using roasting and grinder tools to increase, on the other hand in relation to packaging processed coffee products with brands/labels, packaging, digital marketing and determining the fair market price of coffee products can increase and can be utilized optimally.